Event-triggered fixed-time resilient control for mobile sensor networks with a Sybil attack and input delay - Zhou, Ding; He, Lei; Cao, Zhigang; Zhang, An; Han Xiaopeng (Zielona Góra: Uniwersytet Zielonogórski)
This study is devoted to the resilient control problem of a mobile sensor network with a Sybil attack and input delay. First, a fixed-time observer is constructed to estimate the state exactly, which makes it possible to calculate the settling time. Then, the delayed system is transformed into a delay-free system by introducing Artstein`s transformation, and a confidence metric is used to tackle the Sybil attack problem, which requires no additional data storage beyond signals.
Keywords: resilient consensus; event-triggered control; Sybil attack; input delay